General Karate: A New Compromise Between Budo and Sport in Modern Western Society - Lozovyy, Anatoliy (International Martial Arts and Culture Journal, 2025)
Background and aim. Karate in Western society has developed along two dominant paradigms, namely Budo and Sport, which reflect fundamentally different institutional logics and value orientations. While existing studies have examined these paradigms independently, limited attention has been given to the possibility of an intermediary competition discipline capable of reconciling philosophical authenticity with competitive legitimacy. This study aims to examine karate competition disciplines as institutional constructs that mediate the relationship between Budo and Sport paradigms.Method. This study employed a qualitative analytical design based on comparative conceptual and document-based analysis. The primary subjects of analysis were competition disciplines as institutional forms, specifically Traditional Karate, General Karate, and Sport Karate recognized by the International Olympic Committee. Normative documents, competition regulations, and organizational frameworks were systematically reviewed and compared across analytical dimensions including training logic, competition objectives, governance structure, evaluation criteria, and philosophical alignment.Result and Discussion. The findings indicate that Traditional Karate and Sport Karate embody distinct institutional logics corresponding to Budo-oriented and sport-oriented paradigms. In contrast, General Karate operates as a hybrid institutional model that integrates standardized competition procedures with style-based training traditions. This configuration enables equitable multi-style participation, preserves stylistic identity, and accommodates both philosophical and competitive priorities. The analysis challenges the assumption that authenticity and competitiveness are inherently incompatible by demonstrating the mediating role of institutional design.Conclusion. This study concludes that General Karate represents a viable institutional compromise that bridges philosophical integrity and competitive engagement within contemporary karate systems. By highlighting competition disciplines as active institutional mechanisms rather than neutral technical arrangements, the study contributes to broader theoretical discussions on sportification, authenticity, and institutional hybridity in martial arts and combat sports. These insights offer a transferable framework for examining similar tensions between tradition and modernization in other globalized physical culture practices.